Executive compensation, strategic competition, and relative performance evaluation theory and evidence - Aggarwal, Raj; Samwick, Andrew (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 1996)
We argue that strategic interactions between firms in an oligopoly can explain the puzzling lack of high-powered incentives in executive compensation contracts written by shareholders whose objective is to maximize the value of their shares. We derive the optimal compensation contracts for managers and demonstrate that the use of high-powered incentives will be limited by the need to soften product market competition. In particular, when managers can be compensated based on their own and their rivals' performance, we show that there will be an inverse relationship between the magnitude of high-powered incentives and the degree of competition in the industry. More competitive industries are characterized by weaker pay-performance incentives. Empirically, we find strong evidence of this inverse relationship in the compensation of executives in the United States. Our econometric results are not consistent with alternative theories of the effect of competition on executive compensation. We conclude that strategic considerations can preclude the use of high-powered incentives, in contrast to the predictions of the standard principal-agent model.